2023
DOI: 10.1177/0143831x231157866
|View full text |Cite
|
Sign up to set email alerts
|

Do they need us? Linking functional indispensability and voice behavior: The role of psychological ownership, job insecurity and organizational ambidexterity

Abstract: This study looked into how workers’ perception of their team’s functional indispensability motivates them to engage in promotive voice behavior. The mediating role of psychological ownership and the moderator roles of job insecurity and organizational ambidexterity were also examined. Data from 820 Portuguese workers from different business sectors were analyzed using multiple regression techniques. Results indicate that perceived functional indispensability is positively associated with employee voice behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…In a study among native Dutch participants, it was found that higher perceived functional indispensability and perceived identity indispensability of ethnic minority groups were both independently associated with a lower sense of ingroup ownership of the country, which, in turn, was related to more positive minority outgroup attitudes (Verkuyten, 2022). Further, in organizational contexts it has been found that perceived functional indispensability of a team increases feelings of shared ownership which, in turn, is positively associated with team members engagement in promotive behaviors (Alves, 2020).…”
Section: Collective Ownershipmentioning
confidence: 96%
“…In a study among native Dutch participants, it was found that higher perceived functional indispensability and perceived identity indispensability of ethnic minority groups were both independently associated with a lower sense of ingroup ownership of the country, which, in turn, was related to more positive minority outgroup attitudes (Verkuyten, 2022). Further, in organizational contexts it has been found that perceived functional indispensability of a team increases feelings of shared ownership which, in turn, is positively associated with team members engagement in promotive behaviors (Alves, 2020).…”
Section: Collective Ownershipmentioning
confidence: 96%